Electrochemical Analysis of Architecturally Enhanced LiFe0.5Mn0.5PO4 Multiwalled Carbon Nanotube Composite - Sabelo Sifuba; Shane Willenberg; Usisipho Feleni; Natasha Ross; Emmanuel Iwuoha (Journal of Nanotechnology)
In this work, the effect of carbon on the electrochemical properties of multiwalled carbon nanotube (MWCNT) functionalized lithium iron manganese phosphate was studied. In an attempt to provide insight into the structural and electronic properties of optimized electrode materials, a systematic study based on a combination of structural and spectroscopic techniques was conducted. The phosphor-olivine LiFe0.5Mn0.5PO4 was synthesized via a simple microwave synthesis using LiFePO4 and LiMnPO4 as precursors. Cyclic voltammetry was used to evaluate the electrochemical parameters (electron transfer and ionic diffusivity) of the LiFe0.5Mn0.5PO4 redox couples. The redox potentials show two separate distinct redox peaks that correspond to Mn2+/Mn3+ (4.1 V vs Li/Li+) and Fe2+/Fe3+ (3.5 V vs Li/Li+) due to interaction arrangement of Fe-O-Mn in the olivine lattice. The electrochemical impedance spectroscopy (EIS) results showed LiFe0.5Mn0.5PO4-MWCNTs have high conductivity with reduced charge resistance. This result demonstrates that MWCNTs stimulate faster electron transfer and stability for the LiFe0.5Mn0.5PO4 framework, which demonstrates to be favorable as a host material for Li+ ions.